Defect characterization in compositionally graded InGaAs layers on GaAs(001) grown by MBE. Issue 11 (24th October 2013) - Sasaki, Takuo; Norman, Andrew G.; Romero, Manuel J.; Al‐Jassim, Mowafak M.; Takahasi, Masamitu; Kojima, Nobuaki; Ohshita, Yoshio; Yamaguchi, Masafumi; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract Defect characterization in molecular beam epitaxial (MBE) compositionally‐graded InxGa1‐xAs layers on GaAs substrates consisting different thickness of overshooting (OS) layers was carried out using cathodoluminescence (CL) and transmission electron microscopy (TEM). We found that the thickness of the OS layer influences not only stress but also lattice defects generated in a top InGaAs layer. While the top InGaAs layer with a thin OS layer is under compression and has mainly threading dislocations, the top layer with a thick OS layer is under tension and exhibits inhomogeneous strain associating with phase separation. We will discuss the mechanisms of defect generation and their in‐plane distribution based on strain relaxation at the top and OS layers. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)